2020
DOI: 10.1213/ane.0000000000004564
|View full text |Cite
|
Sign up to set email alerts
|

Parsimony of Hemodynamic Monitoring Data Sufficient for the Detection of Hemorrhage

Abstract: BACKGROUND: Individualized hemodynamic monitoring approaches are not well validated. Thus, we evaluated the discriminative performance improvement that might occur when moving from noninvasive monitoring (NIM) to invasive monitoring and with increasing levels of featurization associated with increasing sampling frequency and referencing to a stable baseline to identify bleeding during surgery in a porcine model. METHODS: We collected physiologic wavefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Following lung function, like looking for signatures of illness, in our view requires continuous recording of organ function: the more highly resolved, the better. Pinsky et al recently demonstrated the additional information of noninvasive and invasive heart rate and waveform data in early detection of hemorrhage in pigs ( 68 , 69 ), affirming clinical studies ( 45 , 70 ). Heart rate analysis is directly applicable to clinical practice—each heartbeat sends an easily detected signal and allows for detailed analysis of long time-series of interbeat intervals using new and old mathematics ( 71 , 72 ).…”
mentioning
confidence: 80%
“…Following lung function, like looking for signatures of illness, in our view requires continuous recording of organ function: the more highly resolved, the better. Pinsky et al recently demonstrated the additional information of noninvasive and invasive heart rate and waveform data in early detection of hemorrhage in pigs ( 68 , 69 ), affirming clinical studies ( 45 , 70 ). Heart rate analysis is directly applicable to clinical practice—each heartbeat sends an easily detected signal and allows for detailed analysis of long time-series of interbeat intervals using new and old mathematics ( 71 , 72 ).…”
mentioning
confidence: 80%
“…Graphical features include the amplitude and time domain features extracted from PPG and ABP, and their first derivative waveform has been widely used for tracking hemodynamics [ 21 , 22 ]. Our previous studies also attempted to use features derived from vital signs and machine learning techniques to detect hemorrhage and reported the ability of PPG-waveform-derived features, heart rate, and BP-derived features in reflecting physiological condition changes in subjects suffering from blood loss [ 18 , 23 , 24 ]. Similar features were extracted as the feature metrics in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Current early hemorrhage detection studies are based on machine learning approaches, where feature normalization by referencing their baseline value could mitigate large subject-to-subject variability [ 16 ]. Pinsky et al reported the efficiency of normalizing features derived by vital signs by referencing their baseline values [ 18 ]. It is thus hypothesized that normalized features derived by vital signs could be potential predictors for tracking hemorrhage and BLV.…”
Section: Introductionmentioning
confidence: 99%
“…We have developed predictive models using controlled animal laboratory data and historical ICU data that demonstrate good performance in predicting clinically relevant tachycardia, hypotension, and bleeding. We also demonstrated the incremental benefit of high-frequency data in increasing the reliability of these prediction models [ 8 , 17 , 39 , 40 , 41 ]. For instance, advanced signal processing predicted clinically relevant tachycardia and hypotension in ICU patients [ 42 , 43 ].…”
Section: Examples Of Forecasting and Phenotyping Instability In The Icumentioning
confidence: 99%